Controlling hemoglobin-mediated lipid oxidation in herring (Clupea harengus) co-products via incubation or dipping in a recyclable antioxidant solution. (July 2021) - Wu, Haizhou; Sajib, Mursalin; Undeland, Ingrid
Abstract: Applying value-adding techniques to fish co-products is rendered difficult due to their high susceptibility to hemoglobin (Hb)-mediated lipid oxidation. In this study, we investigated a dipping technology with a solution containing Duralox MANC 213- a mixture of rosemary extract, ascorbic acid, tocopherols and citric acid – to control lipid oxidation during storage at 0 °C and 20 °C. The possibilities to re-use the antioxidant solution was also analyzed, along with studies on the link between Duralox MANC and Hb-form. Dipping in Duralox MANC largely increased the oxidation lag phase; from <0.5 to >3.5 d at 20 °C, and from <1 d to >11 d at 0 °C. Even after re-use of the solution up to 10 times, lipid oxidation was completely inhibited at 0 °C. Duralox MANC could prevent auto-oxidation and hemin loss of herring Hb; which are suggested as the main mechanisms behind the observed stabilization of herring co-products against lipid oxidation. Highlights: Lipid oxidation developed within 1/0.5 days in minced herring co-products at 0/20 °C. Pre-incubation with antioxidant (Duralox-MANC) remarkably inhibited lipid oxidation. The antioxidant solution could be re-used up to 10 times with maintained activity. Duralox-MANC prevented auto-oxidation and hemin loss from herring Hb. The incubation strategy facilitates for further value-adding of herring co-products.